Catherine Urner, Charles Koechlin and The Bride of God - Moore, Christopher (Les Cahiers de la Société québécoise de recherche en musique)

(untitled) (Société québécoise de recherche en musique, 2015)
Developing upon recent studies by Barbara Urner Johnson and Robert Orledge, this article examines the pedagogical relationship and musical collaborations between French composer Charles Koechlin and his American student and lover, Catherine Urner. Drawing on the unpublished manuscripts of their most important collaborative work, the symphonic poem The Bride of God (1924-1929), this article traces the chronology and nature of their collaboration, outlines the work’s narrative structure, and argues that Urner’s input was more important than has been previously claimed. The article also highlights elements of Urner’s compositional style and techniques and shows that while she may have been indebted to Koechlin’s musical and aesthetic influence throughout the 1920s, when their intimate relationship ceased, she was compelled to explore new compositional paths. Ultimately, this article offers a preliminary sketch of Urner’s musical trajectory throughout the 1920s and early 1930s as well as the important roles that Koechlin assumed in her musical development.